Perceived Organizational Support and Performance: The Mediating Effect of Affective Values - Endang Sulistiyani (Jurnal Manajemen Bisnis, 2022)
Research aims: The purpose of this study is to analyze several antecedent variables that affect lecturer performance, namely perceived organizational support, affective values, and academic culture.Design/Methodology/Approach: The population of this research was the lecturers of the Politeknik Negeri Semarang. The sampling method used purposive sampling. Data collection methods were by distributing questionnaires, interviews, observation, and literature study. The data were analyzed using the Structural Equation Modeling technique. Research findings: Based on statistical results, four hypotheses proposed showed a significant positive effect on all relationships between variables. The indirect effect of the independent variable on the lecturer's performance produces a strategy, improving the lecturer's performance through affective values. In addition, the dominant influence between variables is shown by the relationship between affective values on the lecturer's performance.Theoretical Contribution/Originality: In accordance with social exchange theory and organizational support theory, there was a mutually beneficial reciprocal relationship between the organization and employees. Socio-emotional needs of lecturers were met when they received good treatment from their leaders, which had implications for the value of employee commitment to organizational progress.Practitioners/Policy Implications: The organization's management team must always support the improvement of the competence and welfare needs of employees. The give-and-take relationship between the organization and employees fosters morale to achieve a common goal. In addition, affective value as a consequent variable of perceived organizational support and academic culture increases the active participation of organizational members to always be proud to be part of the organization and adapt to challenging tasks as self-actualization.Research Limitations/Implications: However, this study only used one research object. Thus, future research needs to consider the research object in all state polytechnics in Indonesia. Such studies are necessary for cross-validating research findings.